Elevated Serum Levels of Stromal-Derived Factor-1α Are Associated with Increased Osteoclast Activity and Osteolytic Bone Disease in Multiple Myeloma Patients - Zannettino, Andrew C.W.; Farrugia, Amanda N.; Kortesidis, Angela; Manavis, Jim; To, L. Bik; Martin, Sally K.; Diamond, Peter; Tamamura, Hirokazu; Lapidot, Tsvee; Fujii, Nobutaka; Gronthos, Stan (Cancer research (Chicago, Ill.), 2005)
Multiple myeloma (MM) is an incurable plasma cell (PC) malignancy able to mediate massive destruction of the axial and craniofacial skeleton. The aim of this study was to investigate the role of the potent chemokine, stromal-derived factor-1α (SDF-1α) in the recruitment of osteoclast precursors to the bone marrow. Our studies show that MM PC produce significant levels of SDF-1α protein and exhibit elevated plasma levels of SDF-1α when compared with normal, age-matched subjects. The level of SDF-1α positively correlated with the presence of multiple radiological bone lesions in individuals with MM, suggesting a potential role for SDF-1α in osteoclast precursor recruitment and activation. To examine this further, peripheral blood–derived CD14+ osteoclast precursors were cultured in an in vitro osteoclast-potentiating culture system in the presence of recombinant human SDF-1α. Although failing to stimulate an increase in TRAP+, multinucleated osteoclast formation, our studies show that SDF-1α mediated a dramatic increase in both the number and the size of the resorption lacunae formed. The increased osteoclast motility and activation in response to SDF-1α was associated with an increase in the expression of a number of osteoclast activation–related genes, including RANKL, RANK, TRAP, MMP-9, CA-II, and Cathepsin K. Importantly, the small-molecule CXCR4-specific inhibitor, 4F-Benzoyl-TE14011 (T140), effectively blocked osteoclast formation stimulated by the myeloma cell line, RPMI-8226. Based on these findings, we believe that the synthesis of high levels of SDF-1α by MM PC may serve to recruit osteoclast precursors to local sites within the bone marrow and enhance their motility and bone-resorbing activity. Therefore, we propose that inhibition of the CXCR4-SDF-1α axis may provide an effective means of treatment for MM-induced osteolysis.